Thematic specialities of the publicistic of Abai Kunanbayuly’s followers - Shauenova Г.Ә. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2025)
At present, in connection with the renewal of public consciousness and views, new judgments have been made from the point of view of studying literary heritage, and historical weighing has been undertaken. Thanks to independence, when looking at our past, analyzing previously published journalistic works, the reality that was sealed as a result of the Prohibition of the Soviet ideology, which was born by the Marxist-Leninist methodology, turned to one-on-one publicity. The article analyzes the special influence of Abai’s heritage on his students, as a result of which the formation of their creativity, their leaders, and their value for society are considered. Hakim analyzes the journalistic world of his students, epistolary texts that firmly convey the socio-social, historical, political, spiritual face of that era, determines their ideological orientation, artistic features and contribution to the national tradition of journalism.Folk problems in the works of Abai’s students are analyzed from the point of view of independence, analysis and conclusions are given. The most acute issues of journalistic heritage (education, enlightenment, settlement, religion, language, etc.) are removed and revised from an independent point of view. Analyzing the works of the leading poets around Hakim, it is proposed to systematize educational and educational journalism; religious and educational journalism; journalism about the Earth, artistic journalism; philosophical journalism; journalism that determined the appearance of the times, etc.